A case report of acute pancreatitis with glycogen storage disease type IA in an adult patient and review of the literature. Issue 42 (16th October 2020) - Ai, Jiaoyu; He, Wenhua; Huang, Xin; Wu, Yao; Lei, Yupeng; Yu, Chen; Görgülü, Kivanc; Diakopoulos, Kalliope N.; Lu, Nonghua; Zhu, Yin
Abstract: Rationale: Glycogen storage disease type IA (GSD IA) is an inherited disorder of glycogen metabolism characterized by fasting hypoglycemia, hyperuricemia, and hyperlipidemia including hypertriglyceridemia (HTG). Patients have a higher risk of developing acute pancreatitis (AP) because of HTG. AP is a potentially life-threatening disease with a wide spectrum severity. Nevertheless, almost no reports exist on GSD IA-induced AP in adult patients. Patient concerns: A 23-year-old male patient with GSD 1A is presented, who developed moderate severe AP due to HTG. Diagnoses: The GSD 1A genetic background of this patient was confirmed by Sanger sequencing. Laboratory tests, along with abdominal enhanced-computed tomography, were used for the diagnosis of HTG and AP. Interventions: This patient was transferred to the intensive care unit and treated by reducing HTG, suppressing gastric acid, inhibiting trypsin activity, and relieving hyperuricemia and gout. Outcomes: Fifteen days after hospital admission, the patient had no complaints about abdominal pain and distention. Follow-up of laboratory tests displayed almost normal values. Reexamination by computed tomography exhibited a reduction in peripancreatic necrotic fluid collection compared with the initial stage. Lessons: Fast and long-term reduction of triglycerides along with management of AP proved effective in relieving suffering of an adult GSD IA-patient and improving prognosis. Thus, therapeutic approaches have to be renewed and standardized to cope with all complications, especially AP, and enable a better outcome so that patients can master the disease.